Framing the startup accelerator through assemblage theory: A case study of an intensive hub in Indonesia. (December 2022) - Luik, Jandy; Hook, Jonathan; Ng, Jenna
This article presents how assemblage theory, as taken from Deleuze and Guattari, can be used to understand the intensive approaches of startup accelerators in supporting startup companies. Through a study of a startup accelerator in Jakarta, Indonesia, we present three snapshots to exemplify manifestations of what we argue as the accelerator's " seed accelerator " form of content and " seed funding " form of expression as well as their reciprocal presupposition to demonstrate the multiplicity of assemblage as the organizational principles of the accelerator. Employing the tenets of formalization and territorialization from assemblage theory to analyze the results, this article shows that the " seed accelerator " form of content is manifested by way of how the accelerator's bodies of its human elements, activities, events, and infrastructure relate and interconnect throughout the accelerator's 12-week program towards its end point, that is, fulfilling the stakes for the Final Demo-Day, while, on the other hand, the " seed funding " form of expression is manifested by way of the usage of terms related to fund-raising, expressions of worry, and the expectations of the hub management and the VC in preparing the startups for the next level of funding. Moreover, we argue that the formalized function of the accelerator assemblage is to intensively seed scalable startups. This assemblage analysis thus offers an interrelational perspective regarding startup accelerators, and demonstrates the value of formalization and territorialization in assemblage theory to understand the programming arrangements in a startup accelerator.